Divergent taxonomic and functional responses of microbial communities to field simulation of aeolian soil erosion and deposition. Issue 16 (14th July 2017) - Ma, Xingyu; Zhao, Cancan; Gao, Ying; Liu, Bin; Wang, Tengxu; Yuan, Tong; Hale, Lauren; Nostrand, Joy D. Van; Wan, Shiqiang; Zhou, Jizhong; Yang, Yunfeng
Abstract: Aeolian soil erosion and deposition have worldwide impacts on agriculture, air quality and public health. However, ecosystem responses to soil erosion and deposition remain largely unclear in regard to microorganisms, which are the crucial drivers of biogeochemical cycles. Using integrated metagenomics technologies, we analysed microbial communities subjected to simulated soil erosion and deposition in a semiarid grassland of Inner Mongolia, China. As expected, soil total organic carbon and plant coverage were decreased by soil erosion, and soil dissolved organic carbon (DOC) was increased by soil deposition, demonstrating that field simulation was reliable. Soil microbial communities were altered ( p < .039) by both soil erosion and deposition, with dramatic increase in Cyanobacteria related to increased stability in soil aggregates. amyA genes encoding α‐amylases were specifically increased ( p = .01) by soil deposition and positively correlated ( p = .02) to DOC, which likely explained changes in DOC. Surprisingly, most of microbial functional genes associated with carbon, nitrogen, phosphorus and potassium cycling were decreased or unaltered by both erosion and deposition, probably arising from acceleration of organic matter mineralization. These divergent responses support the necessity to include microbial components in evaluating ecological consequences. Furthermore, Mantel tests showed strong, significant correlations between soil nutrients and functional structure but not taxonomic structure, demonstrating close relevance of microbial function traits to nutrient cycling.